The effects of consuming mineral water from the "Topla Voda" spring on the body composition and functional and biochemical parameters of professional male handball athletes: a pilot study - Batinic, D.; Djuranovic, A.; Maletic, M.; Stankovic, S.; Zivkovic, V.; Stanojevic, D.; Bolevich, S.; Savic, M.; Jakovljevic, V. (Sports, 2025)
Adequate hydration is crucial to an athlete`s health and performance. There is some evidence that the different compositions of various mineral water types may improve exercise performance and affect different biomarkers. The aim was to investigate the consumption of mineral water from the "Topla voda" spring in terms of its safety profile and its effect on body composition and functional and biochemical parameters in professional athletes. During the preparation phase of their mesocycle, 14 male professional handball players underwent a complete sports medical screening exam with a cardiopulmonary exercise test (CPET), blood gas analysis, and oxidative stress marker dynamics taken at four points during the CPET. The athletes were then randomized into two equal groups; the first group consumed mineral water, and the second group consumed tap water. After four weeks, the biochemical analysis and CPET were repeated. Routine analyses showed that the "mineral water" group had increased their mean corpuscular hemoglobin (ANCOVA = 0.050) and mean corpuscular hemoglobin concentration (ANCOVA = 0.001) and had a greater metabolic equivalent of task (MET) value at the end of the test (ANCOVA = 0.049), with no significant changes in the other measured parameters. Consuming "mineral water" appears to be safe, with some potential positive effects compared with tap water, mostly in terms of hemoglobin parameters and exercise tolerance.